Atrial fibrillation with high ventricular rate in emergency room: What’s the best strategy for treatment? - SOEIRO,ALEXANDRE DE MATOS (2016)
SUMMARY Atrial fibrillation (AF) is the most common arrhythmia in clinical practice and can lead to significant decline in functional status and quality of life among affected patients. The risk of developing AF increases with age and the presence of structural heart disease. Thus, the attendance of patients with high ventricular response to AF is common, which makes knowledge of its management mandatory. In this context, the choice of heart rate and/or rhythm control therapy is fundamental and complex, with multiple possibilities. Thus, this review aims to assist in the management of these patients, systematizing their care.